The effect of parental presence on the anxiety during first dental treatment in children - Serhat Karaca; Belen Şirinoğlu Capan (Medical Journals Sweden, 2024)
Objective: The aim of this study was to evaluate the effect of parental presence on dental anxiety in children during dental treatments. Materials and methods: The study was conducted with 194 children between January-April, 2020. The children were randomly divided into two subgroups. Children in group-I were treated in parent's presence (pp), and in group-II in parent's absence (pa). The Wong-Baker FACES Pain Rating Scale (WBFPS) and The Modified Dental Anxiety Scale (MDAS) were used for subjective measurements, whereas the objective measurement was performed by measuring the heart rate. Results: The mean age of 194 children was 6.26 ± 1.15 years, ranging from 5-8 years of age. The mean MDAS score of all children was 15.1 ± 4.72. No significant correlations were found in terms of dental anxiety between the children's gender and age with heart rate, WBFPS and MDAS scores. Preoperative WBFPSscores (6.83 ± 1.04 pp and 7.01 ± 0.93 pa) were higher than postoperative scores (5.34 ± 2.11 pp and 5.74 ± 2.04 pa), with no statistically significant difference. Although there was no statistically significant results, the paediatric dentist observed a deterioration in the children's behavior throughout the sessions in group-II compared to children in group-I. Conclusions: Parental presence has no statistically significant effect on dental anxiety in children during dental treatments.